Evaluation the Efficiency of Magnesium Oxide Nanoparticles in the Reduction of Ochratoxin A and in the Inhibition of Asperillusniger - Shahbaa H Majeed (Journal of Global Pharma Technology, 2020)
This study was conducted in Mycotoxins Laboratory /Department of Plant Protection/College of Agriculture at" University of Baghdad". This study aimed to determine the efficiency of magnesium oxide nanoparticles (MgO) (NP) in the inhibition of Aspergillusniger growth and in the degradation ocra a toxin. The results found that MgOnanoparticles significantly inhibited the growth of A. niger. There were significant differences between all the concentrations of MgOnanoparticles in comparison to control groups, while no significant difference was fund between the concentration of 2% and 3%;a significant differences also was detected between the concentrations (2 and 3)% for the first concentration (1%) and the 95% for concentration of(3%). Moreover, the results observed that MgO nanoparticles was potential in the reduction of ocra Atoxin A that produced from A. nigerusing Performance liquid chromatography (HPLC) technique; the percentage of reduction of toxin were 90.1%, 92.2%, 93.7% for concentrations of NaO2 1%, 2% and 3% respectively, however the best reduction percentage was 92.2% with concentration of 0.06 μg/kg after the treatment with MgOnanoparticles at 2%. Keywords: Ochratoxin A, MgO (NP), inhibition of Aspergillusniger, Reduction.